Validade e confiabilidade da Movement Assessment Battery For Children - 2ª edição para crianças brasileiras de 4 a 8 anos de idade - Carolinne Linhares Pinheiro (2015)
The motor test of the Movement Assessment Battery for Children 2 (MABC-2, one of the resources most utilized to detect mild to moderate motor difficulties in children 3-16 years old, has been used in Brazil and while there is a validity study, there is no study comparing the performance of Brazilian children with the normative sample of the instrument. The objective of this study was to compare the performance of Brazilian (BR) children 4-8 years old with the United Kingdom (UK) normative sample on individual items, areas and the total score of the MABC-2, as well as analyze the test retest reliability for Brazilian children ages 4, 6 and 8 years old. In the comparative study, data on 883 typically developing children (396 BR and 487 UK) were analyzed; for test retest reliability, 51 Brazilian children enrolled in schools in the city of Rio de Janeiro / RJ were evaluated twice with the MABC-2. Means and standard deviations were calculated for the scores of each item, for each area and t-test (p = 0.05) was used to compare the performance between groups considering age and gender For test-retest reliability, children were reassessed with a mean interval of 13 days and the intraclass correlation coefficient (ICC) was calculated for individual items in each age group, and for the areas and overall test result; Kappa index was used to verify the agreement on the final classification. Significant differences between groups were found for different items in several ages, which were more recurrent for the items 'Drawing trail" and "Hitting targets. Considering the test areas, differences between the groups occurred in 'Manual Dexterity', for children of 5, 6, 7 and 8 years old, Aim and catch and in the total test score for children 4 years and a half, 7 and 8 years old. In almost all situations, underperformance of the Brazilian children was identified. Brazilian girls showed worse performance than the British in various items and age groups. Test retest reliability values were quite variable for individual items and more consistent for areas and overall test result, with poor to moderate ICC values for all three areas (0.60 to 0.69) and good (0.78) for the total test score. Kappa Index (0.67) indicated good agreement between the two assessments for the test´s final motor diagnosis. The differences between groups in items, areas, and total test score suggest cross-cultural differences that lead us to question the validity of the UK norms for the Brazilian children. These results are consistent with studies using the first edition of the test in other countries. The differences may be related to socioeconomic factors